Pharmacokinetics and pharmacodynamics of dapagliflozin in combination with insulin in Japanese patients with type 1 diabetes. Issue 4 (21st December 2018) - Watada, Hirotaka; Shiramoto, Masanari; Ueda, Shinya; Tang, Weifeng; Asano, Michiko; Thorén, Fredrik; Kim, Hyosung; Yajima, Toshitaka; Boulton, David W.; Araki, Eiichi
Abstract : Aims: To assess the pharmacokinetics/pharmacodynamics (PK/PD) of dapagliflozin, a sodium‐glucose co‐transporter 2 inhibitor that increases urinary glucose excretion (UGE) and its major metabolite, dapagliflozin‐3‐O‐glucuronide (D3OG), in Japanese patients with type 1 diabetes (T1D) and inadequate glycaemic control (HbA1c 7%‐10%). Materials and methods: Japanese patients (18‐65 years) with inadequately controlled T1D were randomized 1:1:1 to dapagliflozin 5 mg, 10 mg or placebo (n = 14 each) once daily for 7 days, with adjustable insulin. The PK/PD characteristics of dapagliflozin and D3OG were assessed on Day 7. Patients underwent follow‐up evaluation on Days 8 and 14. Adverse events (AEs), hypoglycaemic episodes and events of diabetic ketoacidosis (DKA) were recorded over the treatment and follow‐up periods. Results: A total of 42 randomized patients received dapagliflozin or placebo. PK variables increased in a dose‐dependent manner. D3OG was generated rapidly, with a median time to maximum plasma concentration of 2.0 hours (1.0‐3.0). The dapagliflozin dose‐UGE relationship was attenuated, with larger insulin dose reductions than anticipated. Mean percent (standard error) changes in total daily insulin dose from baseline to Day 7 were − 36.86% (3.32), −39.13% (2.68) and − 4.97% (5.28) for dapagliflozin 5 mg and 10 mg and for placebo, respectively. No DKA was reported. AEs were consistent with the established dapagliflozin safety profile. There was no increase in hypoglycaemia. Conclusions: The PK and safety profiles of dapagliflozin in Japanese patients with T1D were consistent with previous studies, but with an unanticipated attenuation of the PD dose‐response measured as UGE.